2003
DOI: 10.1021/ol034589t
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Trimerization of [(S)R]-[(p-Tolylsulfinyl)methyl]-p-quinols and p-Quinamines

Abstract: [reaction: see text] The asymmetric synthesis of pentacyclic derivatives was achieved in a single step starting from enantiopure [(S)R]-[(p-tolylsulfinyl)methyl]-p-quinols or the nitrogen analogue, through a domino sequence involving four conjugate additions in excellent yields. Eight new stereogenic centers were created in one step and in a highly diastereoselective manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…The spontaneous decomposition of 61 afforded material whose identity could not be established conclusively. However, Spivey has reported55 that a closely related 4‐hydroxycyclohexenone (±)‐ 63 undergoes dimerisation through oxy‐Michael addition affording a diastereomeric mixture of products (±)‐ 64 (Scheme ); analogous processes have also been reported 56. In the example at hand, 61 possesses two oxygen nucleophiles, so scope exists for formation of numerous isomeric dimers, acetonide migration and/or polymerisation.…”
Section: Resultsmentioning
confidence: 97%
“…The spontaneous decomposition of 61 afforded material whose identity could not be established conclusively. However, Spivey has reported55 that a closely related 4‐hydroxycyclohexenone (±)‐ 63 undergoes dimerisation through oxy‐Michael addition affording a diastereomeric mixture of products (±)‐ 64 (Scheme ); analogous processes have also been reported 56. In the example at hand, 61 possesses two oxygen nucleophiles, so scope exists for formation of numerous isomeric dimers, acetonide migration and/or polymerisation.…”
Section: Resultsmentioning
confidence: 97%
“…Many domino reaction sequences have been reported that involve initial addition of the p ‐quinol alcohol onto an electrophile with subsequent 5‐ exo ‐ trig cyclization to generate a new fused five‐membered ring (Scheme a) . One of the most complex examples of a multiple‐bond‐forming reaction involving p ‐quinols comes from the Carreño laboratory, where they demonstrated that [( p ‐tolylsulfinyl)methyl]‐ p ‐quinol can participate in a spectacular, albeit unique, quadruple domino reaction sequence to form a pentacyclic trimer (Scheme b) …”
Section: Methodsmentioning
confidence: 99%
“…[4] One of the most complex examples of am ultiple-bond-forming reaction involving pquinols comes from the CarreÇo laboratory,w here they demonstrated that [(p-tolylsulfinyl)methyl]-p-quinol can participate in as pectacular,a lbeit unique,q uadruple domino reaction sequence to form ap entacyclic trimer (Scheme 1b). [5] In our own laboratory,wehave achieved ashort biomimetic synthesis of the natural products (AE)-incarviditone and (AE)-incarvilleatone through dimerization of (AE)-rengyolone, a p-quinol-derived natural product (Scheme 1c). [6] Herein, we describe our exploration of this biomimetic strategy with simple and more readily available p-quinols,t oa ccess unnatural structures of even greater molecular complexity than the originally targeted natural products (Scheme 1d).…”
mentioning
confidence: 99%
“…The p-quinol 89 evolved, in the presence of NaH, through a domino sequence of four conjugate additions, giving a trimerisation process. 61…”
Section: Asymmetric Conjugate Additionsmentioning
confidence: 99%